Electrolyte additive, electrolyte and lithium ion battery
By using a combination of film-forming additives and leveling agents in lithium-ion batteries, the problems of electrode-electrolyte interface and lithium dendrites are solved, and the battery has good circulation performance and safety is achieved.
Patent Information
- Application Number
- CN202510175652.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-18
AI Technical Summary
There are problems in lithium-ion batteries with electrode-electrolyte interfaces and lithium dendrites growth, which affect the cycling performance and safety of the battery.
Using an electrolyte additive, including the film-forming additive 4-dimethylaminophenylthioisocyanate compound and the leveling agent 2-mercaptobenzimidazole, a stable interface film is constructed through the film-forming additive, and the growth of lithium dendrites is inhibited by the leveling agent.
Through synergistic action, the better circulation performance and good safety of lithium-ion batteries are achieved, and the growth of lithium dendrites and the volume deformation of the electrode material during the circulation are avoided.
Smart Images

Figure CN119650859B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to an electrolyte additive, an electrolyte and a lithium ion battery. Background Art
[0002] With the rapid development of modern electronic products, new energy vehicles and energy storage systems, people are increasingly looking forward to higher energy density power batteries. Currently, commercial lithium-ion batteries are mainly carbonate-based electrolytes, which cannot meet people's demand for high energy density electrochemical energy storage devices. It is necessary to develop new electrolyte systems to match new high energy density electrode materials. The properties of the electrolyte affect the interface stability, thermodynamic stability and Li + The transfer kinetics at the electrode / electrolyte interface and the addition of additives to the electrolyte can obtain an in-situ generated CEI / SEI film, thereby improving the coulombic efficiency and cycle stability of the battery, which is an effective method that is both economical and practical. Summary of the invention
[0003] The present invention aims to provide an electrolyte additive, an electrolyte and a lithium ion battery to solve the problems of instability of the electrode-electrolyte interface and growth of lithium dendrites.
[0004] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:
[0005] An electrolyte additive comprises a film-forming additive and a leveling agent, wherein the film-forming additive is a 4-dimethylaminophenylthioisocyanate compound, the leveling agent is 2-mercaptobenzimidazole, the added mass percentage of the film-forming additive in the electrolyte is 0.5-2%, and the added mass percentage of the leveling agent in the electrolyte is 0.2-1%.
[0006] Since the highly reactive lithium element in the negative electrode will spontaneously react with the non-aqueous electrolyte to form an unstable solid electrolyte interface, there is also a risk of lithium dendrite growth at the negative electrode. There are currently two main approaches to the above problem: one is to construct a solid interface film to inhibit the side reaction between the electrolyte and the negative electrode; the other is to regulate the uniform Li + The above two ideas can be realized through the additive strategy which is simple to operate and low in cost, that is, adding film-forming additives to participate in optimizing the interface layer components, and using the leveling agent in the electroplating industry to induce uniform lithium deposition. The synergistic effect of the two can achieve better cycle performance and good safety of lithium-ion batteries.
[0007] The electrolyte additives of the present invention include film-forming additives and leveling agents. The film-forming additives participate in the construction and regulation of the components of the interface film through preferential redox reactions, thereby effectively improving its stability and firmness. The leveling agent is used to spontaneously adsorb on the negative electrode surface and react with Li+ The strong coordination ability of the leveler-Li + The complex will repel Li + Push to the adjacent area to avoid Li + Specifically, 4-dimethylaminophenylthioisocyanate compounds have preferential redox ability and can construct an interface layer rich in high-quality inorganic components (such as LiF, Li3N, Li2S, Li2SO4, etc.), giving the interface layer good Li + The transport capacity of 2-mercaptobenzimidazole and Li + It has strong coordination ability and can spontaneously adsorb on the negative electrode surface to act as a molecular protective layer, especially at the protrusions, effectively inhibiting Li + The electrolyte additive of the present invention provides a novel additive combination. Through the synergistic effect of the film-forming additive and the leveling agent, a stable interface film is constructed by the film-forming additive, and uniform lithium deposition is induced by the leveling agent. When the two are added to the electrolyte system at the same time, they do not interfere with each other, which helps to achieve better cycle performance and good safety of lithium-ion batteries.
[0008] As a further preference, the added mass percentage of the film-forming additive in the electrolyte is 1%, and the added mass percentage of the leveling agent in the electrolyte is 0.5%.
[0009] Preferably, the structure of the film-forming additive is as shown in formula (1):
[0010]
[0011] Formula (1),
[0012] Wherein, R1 to R4 are each independently selected from at least one of a hydrogen atom, a fluorine atom, a cyano group, a nitro group, an isothiocyanate group, and a fluoroalkyl group.
[0013] An electrolyte comprises the electrolyte additive as described above, and further comprises a lithium salt and an organic solvent.
[0014] Preferably, the lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonyl imide and lithium bis(fluorosulfonyl) imide.
[0015] Preferably, the concentration of the lithium salt in the electrolyte is 0.5-2 mol / L.
[0016] As further preferred, the concentration of the lithium salt in the electrolyte is 1 mol / L.
[0017] Preferably, the organic solvent comprises cyclic carbonate and chain carbonate, the cyclic carbonate is any one or a combination of ethylene carbonate and propylene carbonate; the chain carbonate is any one or a combination of diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0018] Preferably, the cyclic carbonate is added to the electrolyte in an amount of 25-35% by mass.
[0019] As a further preference, the mass percentage of the cyclic carbonate added to the electrolyte is 28%.
[0020] Preferably, the added mass percentage of the chain carbonate in the electrolyte is 52-58%.
[0021] As a further preference, the added mass percentage of the chain carbonate in the electrolyte is 56%.
[0022] A lithium ion battery comprises a positive electrode, a negative electrode, a separator, and also the electrolyte as described above.
[0023] Preferably, the positive electrode is a high nickel positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0024] Therefore, the present invention has the following beneficial effects:
[0025] (1) The electrolyte additives of the present invention include film-forming additives and leveling agents. The film-forming additives participate in the construction and regulation of the components of the interfacial film through preferential redox reactions, thereby effectively improving its stability and firmness. The leveling agent is used to spontaneously adsorb on the negative electrode surface and react with Li + The strong coordination ability of the leveler-Li + The complex will repel Li + Push to the adjacent area to avoid Li + The random nucleation of Li-ions can inhibit the growth of Li-dendrites.
[0026] (2) The electrolyte additive of the present invention provides a novel additive combination. Through the synergistic effect of the film-forming additive and the leveling agent, a stable interfacial film is constructed by the film-forming additive, and uniform lithium deposition is induced by the leveling agent. When the two are added to the electrolyte system at the same time, they do not interfere with each other, which helps to achieve better cycle performance and good safety of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1It is a curve graph showing the variation of overpotential of the lithium symmetric battery in Examples 1 to 3 and Comparative Example 1 with time.
[0028] Figure 2 It is a curve graph showing the variation of overpotential of the lithium symmetric battery in Example 1, Examples 4-5 and Comparative Example 1 with time.
[0029] Figure 3 It is a curve diagram showing the variation of overpotential of the lithium symmetric battery in Example 1 and Comparative Examples 1 to 3 with time.
[0030] Figure 4 It is a long cycle performance diagram of the Li / NCM811 half-cell in Example 1 and Comparative Examples 1 to 3.
[0031] Figure 5 The SEM images of lithium deposition morphology of the Li / NCM811 half-cells in Example 1 and Comparative Examples 1 to 3 after 200 cycles.
[0032] Figure 6 This is a long cycle performance diagram of the C / NCM811 soft-pack lithium-ion battery in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment provides an electrolyte additive, an electrolyte containing the electrolyte additive, and a lithium ion battery containing the electrolyte.
[0036] An electrolyte additive includes a film-forming additive and a leveling agent, wherein the film-forming additive is 0.1 g of 4-dimethylaminophenylthioisocyanate (A), and the leveling agent is 0.05 g of 2-mercaptobenzimidazole (Z). The added mass percentage of 4-dimethylaminophenylthioisocyanate (A) in 9.85 g of the electrolyte is 1%, and the added mass percentage of 2-mercaptobenzimidazole (Z) in 9.85 g of the electrolyte is 0.5%. The structure of the film-forming additive is shown in formula (2):
[0037]
[0038] Formula (2).
[0039] An electrolyte, comprising the electrolyte additive as described above, further comprising lithium hexafluorophosphate (LiPF6) and an organic solvent. The organic solvent comprises ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The concentration of LiPF6 in the electrolyte is 1 mol / L, the added mass percentage of EC in the electrolyte is 28%, and the added mass percentage of DMC and EMC in the electrolyte is 56% (DMC: EMC=1:1, wt%).
[0040] A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte as described above. The positive electrode is a high-nickel positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2 or lithium sheet, the negative electrode is lithium sheet or graphite negative electrode, and the diaphragm is Celgard3501.
[0041] Example 2
[0042] The difference between this embodiment and embodiment 1 is that:
[0043] An electrolyte additive, wherein the mass percentage of 2-mercaptobenzimidazole (Z) added to the electrolyte is 0.2%. Others are the same as in Example 1.
[0044] Example 3
[0045] The difference between this embodiment and embodiment 1 is that:
[0046] An electrolyte additive, wherein the mass percentage of 2-mercaptobenzimidazole (Z) added to the electrolyte is 1%. Other aspects are the same as those in Example 1.
[0047] Example 4
[0048] The difference between this embodiment and embodiment 1 is that:
[0049] An electrolyte additive, wherein the mass percentage of 4-dimethylaminophenylthioisocyanate (A) added to the electrolyte is 0.5%. Others are the same as in Example 1.
[0050] Example 5
[0051] The difference between this embodiment and embodiment 1 is that:
[0052] An electrolyte additive, wherein the mass percentage of 4-dimethylaminophenylthioisocyanate (A) added to the electrolyte is 2%. Others are the same as in Example 1.
[0053] Example 6
[0054] The difference between this embodiment and embodiment 1 is that:
[0055] An electrolyte, wherein the organic solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The concentration of LiPF6 in the electrolyte is 0.5 mol / L, the added mass percentage of EC in the electrolyte is 25%, and the added mass percentage of DMC and EMC in the electrolyte is 58% (DMC: EMC=1:1, wt%). Others are the same as in Example 1.
[0056] Example 7
[0057] The difference between this embodiment and embodiment 1 is that:
[0058] An electrolyte, wherein the organic solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The concentration of LiPF6 in the electrolyte is 2 mol / L, the added mass percentage of EC in the electrolyte is 35%, and the added mass percentage of DMC and EMC in the electrolyte is 52% (DMC: EMC=1:1, wt%). Others are the same as in Example 1.
[0059] Example 8
[0060] This embodiment provides a method for preparing a pole piece.
[0061] A method for preparing a pole piece comprises the following steps:
[0062] Commercial NCM811, PVDF, and acetylene black were mixed in a mass ratio of 8:1:1, and 1.8-2 mL of N-methylpyrrolidone solution was added, and stirred in a glove box for 6-8 h. Then, the mixture was coated on aluminum foil with a 100 μm scraper. After coating, the mixture was dried in an oven at 80°C for 2 h, and immediately cut into electrodes with a diameter of 12 mm using a slicer. The cut electrodes were placed in a 120°C oven for vacuum drying for 12 h, and immediately stored in a glove box.
[0063] This embodiment also provides a button battery assembly method.
[0064] A button battery assembly method comprises the following steps:
[0065] The negative electrode shell, gasket, stainless steel sheet, negative electrode sheet, diaphragm, positive electrode sheet, and positive electrode shell were assembled into a button battery in sequence. The amount of electrolyte added was 40 μL, the diaphragm used was Celgard 3501, and the battery was compressed under a nominal pressure of 50 kPa and allowed to stand for 6 to 8 hours before electrochemical testing.
[0066] This embodiment also provides a soft-pack battery assembly method.
[0067] A soft pack battery assembly method comprises the following steps:
[0068] The nickel-rich positive electrode sheet, separator (Celgard 3501), and artificial graphite negative electrode sheet were wound in sequence to obtain a bare battery cell, which was then packaged with aluminum-plastic film, baked, injected, allowed to stand, formed, clamped and resealed before being electrochemically tested.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is:
[0071] An electrolyte includes lithium hexafluorophosphate (LiPF6) and an organic solvent. The organic solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The concentration of LiPF6 in the electrolyte is 1 mol / L, the added mass percentage of EC in the electrolyte is 28%, and the added mass percentage of DMC and EMC in the electrolyte is 56% (DMC: EMC=1:1, wt%). That is, no electrolyte additives are added to the electrolyte. The rest is the same as in Example 1.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is:
[0074] An electrolyte additive, wherein only a film-forming additive is included, the film-forming additive is 4-dimethylaminophenylthioisocyanate (A), and the mass percentage of 4-dimethylaminophenylthioisocyanate (A) added to the electrolyte is 1%. Others are the same as in Example 1.
[0075] Comparative Example 3
[0076] The difference between this comparative example and Example 1 is:
[0077] An electrolyte additive, wherein only a leveling agent is included, the leveling agent is 2-mercaptobenzimidazole (Z), and the mass percentage of 2-mercaptobenzimidazole (Z) added to the electrolyte is 0.5%. Others are the same as in Example 1.
[0078]
Performance test and result analysis
[0079] [The influence of different addition amounts of leveling agent]
[0080] Electrolyte additives were prepared according to the formulas in Examples 1 to 3 and Comparative Example 1, and electrolyte systems with different mass fractions were further obtained. Among them, the electrolyte systems obtained in Examples 1 to 3 and Comparative Example 1 were recorded as A-1%+Z-0.5%, A-1%+Z-0.2%, A-1%+Z-1%, and BE, respectively. Then, lithium symmetric button cells (both positive and negative electrodes were lithium sheets) were assembled according to the method in Example 8, with an electrolyte addition amount of 40 μL (twice) and a diaphragm of Celgard 3501. The assembled lithium symmetric battery was charged at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The capacity density of the lithium symmetric battery was charged and discharged to record the change of the battery overpotential over time. The curve of the change of the overpotential of the lithium symmetric battery in Examples 1 to 3 and Comparative Example 1 over time is shown in Figure 1 shown.
[0081] Depend on Figure 1 It can be seen that on the basis of adding 1% of the film-forming additive 4-dimethylaminophenylthioisocyanate (A), the mass fraction of the added leveler 2-mercaptobenzimidazole (Z) is changed, showing that the lithium symmetric battery (Example 1) adding 0.5% of the leveler 2-mercaptobenzimidazole (Z) shows the smallest polarization at 500h, and is significantly better than the lithium symmetric battery (Comparative Example 1) without adding 4-dimethylaminophenylthioisocyanate (A) and 2-mercaptobenzimidazole (Z).
[0082] [The influence of different addition amounts of film-forming additives]
[0083] Electrolyte additives were prepared according to the formulas in Example 1, Examples 4-5 and Comparative Example 1, and electrolyte systems with different mass fractions were further obtained. Among them, the electrolyte systems obtained in Example 1, Examples 4-5 and Comparative Example 1 were recorded as A-1%+Z-0.5%, A-0.5%+Z-0.5%, A-2%+Z-0.5%, and BE, respectively. Then, lithium symmetrical button cells (both positive and negative electrodes were lithium sheets) were assembled according to the method in Example 8, the amount of electrolyte added was 40 μL (twice), and the separator was Celgard3501. The assembled lithium symmetrical battery was charged at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The capacity density of the lithium symmetric battery was charged and discharged to record the change of the battery overpotential over time. The curve of the change of the overpotential of the lithium symmetric battery in Example 1, Examples 4-5 and Comparative Example 1 over time is shown in FIG. Figure 2 shown.
[0084] Depend on Figure 2It can be seen that on the basis of adding 0.5% of the leveling agent 2-mercaptobenzimidazole (Z), the mass fraction of the added film-forming additive 4-dimethylaminophenylthioisocyanate (A) is changed, showing that the lithium symmetric battery (Example 1) with the addition of 1% of the film-forming additive 4-dimethylaminophenylthioisocyanate (A) shows the smallest polarization at 500h, and is significantly better than the lithium symmetric battery (Comparative Example 1) without the addition of 4-dimethylaminophenylthioisocyanate (A) and 2-mercaptobenzimidazole (Z).
[0085]
Effects of different electrolyte systems on lithium symmetric batteries
[0086] Electrolyte additives were prepared according to the formulas in Example 1 and Comparative Examples 1 to 3, and electrolyte systems with different mass fractions were further obtained. Among them, the electrolyte systems obtained in Example 1 and Comparative Examples 1 to 3 were recorded as A-1%+Z-0.5%, BE, A-1%, and Z-0.5% respectively. Then, lithium symmetrical button cells (both positive and negative electrodes were lithium sheets) were assembled according to the method in Example 8, with an electrolyte addition amount of 40 μL (twice) and a diaphragm of Celgard 3501. The assembled lithium symmetrical battery was charged at 0.5 mA / cm 2 The current density is 0.5 mAh / cm 2 The capacity density of the lithium symmetric battery was charged and discharged to record the change of the battery overpotential over time. The curves of the change of the overpotential of the lithium symmetric battery in Example 1 and Comparative Examples 1 to 3 over time are shown in FIG. Figure 3 shown.
[0087] Depend on Figure 3 It can be seen that the lithium symmetric battery with the simultaneous addition of 1.0% film-forming additive 4-dimethylaminophenylthioisocyanate (A) and 0.5% leveler 2-mercaptobenzimidazole (Z) shows the smallest polarization at 500h, which is better than the lithium symmetric battery with only 1.0% film-forming additive 4-dimethylaminophenylthioisocyanate (A) added, only 0.5% leveler 2-mercaptobenzimidazole (Z) added, and no 4-dimethylaminophenylthioisocyanate (A) and 2-mercaptobenzimidazole (Z) added, indicating that there is a synergistic effect between the film-forming additive and the leveler.
[0088] [Effects of different electrolyte systems on Li / NCM811 half-cells]
[0089] Electrolyte additives were prepared according to the formulas in Example 1 and Comparative Examples 1 to 3, and electrolyte systems with different mass fractions were further obtained. The electrolyte systems obtained in Example 1 and Comparative Examples 1 to 3 were recorded as A-1%+Z-0.5%, BE, A-1%, and Z-0.5% in sequence. Then, Li / NCM811 button half-cells (negative electrode was a lithium sheet, positive electrode was a LiNi with a diameter of 12 mm and a coating thickness of 100 μm) were assembled according to the method in Example 8. 0.8 Co 0.1 Mn 0.1 O2 positive electrode sheet), the electrolyte addition amount is 40μL (twice), and the separator is Celgard 3501. The assembled Li / NCM811 half-cell is subjected to constant current charge and discharge test at a capacity density of 180mAh / g. The long cycle performance of the Li / NCM811 half-cell in Example 1 and Comparative Examples 1 to 3 is shown in the figure Figure 4 The SEM images of lithium deposition morphology of the Li / NCM811 half-cells in Example 1 and Comparative Examples 1 to 3 after 200 cycles are shown in FIG. Figure 5 shown.
[0090] Depend on Figure 4 It can be seen that the Li / NCM811 half-cell with the addition of 1.0% of the film-forming additive 4-dimethylaminophenylthioisocyanate (A) and 0.5% of the leveler 2-mercaptobenzimidazole (Z) showed the highest capacity retention rate at 200 cycles, which was better than the Li / NCM811 half-cell with only 1.0% of the film-forming additive 4-dimethylaminophenylthioisocyanate (A), only 0.5% of the leveler 2-mercaptobenzimidazole (Z), and no 4-dimethylaminophenylthioisocyanate (A) and 2-mercaptobenzimidazole (Z). This shows that the two additives, the film-forming additive and the leveler, successfully constructed a stable solid electrolyte interface and inhibited the growth of lithium dendrites.
[0091] Depend on Figure 5 It can be seen that the lithium negative electrode using conventional ester electrolyte shows a large amount of lithium dendrite morphology after 200 cycles (Comparative Example 1), while the lithium negative electrode adding only 1.0% of the film-forming additive 4-dimethylaminophenylthioisocyanate (A) and only 0.5% of the leveling agent 2-mercaptobenzimidazole (Z) both show fewer lithium dendrites and denser deposition. Under the synergistic effect of the two, the lithium dendrites almost disappear, and the lithium surface becomes smoother and denser.
[0092] [Effects of different electrolyte systems on soft-pack lithium-ion batteries]
[0093] Electrolyte additives were prepared according to the formulas in Example 1 and Comparative Example 1, and electrolyte systems with different mass fractions were further obtained. The electrolyte systems obtained in Example 1 and Comparative Example 1 were recorded as A-1%+Z-0.5% and BE, respectively. Then, C / NCM811 soft-pack lithium-ion batteries were assembled according to the method in Example 8. The assembled soft-pack lithium-ion batteries were subjected to constant current charge and discharge tests at a capacity density of 180 mAh / g. The long cycle performance of the soft-pack lithium-ion batteries in Example 1 and Comparative Example 1 is shown in the figure. Figure 6 shown.
[0094] Depend on Figure 6 It can be seen that the capacity of the soft-pack lithium-ion battery using conventional ester electrolyte decays to 70.7% of the initial capacity after 600 cycles, while the soft-pack battery with 1.0% film-forming additive 4-dimethylaminophenylthioisocyanate (A) and 0.5% leveling agent 2-mercaptobenzimidazole (Z) added simultaneously has a capacity retention rate of up to 79.9% after 738 cycles, which is due to the significant inhibition of lithium dendrites by the two additives and the effective regulation of the electrode-electrolyte interface.
[0095] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.
Claims
1. An electrolyte additive, characterized in that: The invention comprises a film-forming additive and a leveling agent, wherein the film-forming additive is a 4-dimethylaminophenylthioisocyanate compound, the leveling agent is 2-mercaptobenzimidazole, the added mass percentage of the film-forming additive in the electrolyte is 0.5-2%, and the added mass percentage of the leveling agent in the electrolyte is 0.2-1%; wherein the structure of the film-forming additive is as shown in formula (1): Wherein, R1 to R4 are each independently selected from at least one of a hydrogen atom, a fluorine atom, a cyano group, a nitro group, an isothiocyanate group, and a fluoroalkyl group.
2. An electrolyte, characterized in that: The electrolyte additive comprises the electrolyte additive as claimed in claim 1, and further comprises a lithium salt and an organic solvent.
3. The electrolyte according to claim 2, characterized in that The lithium salt is any one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonyl imide, and lithium bis(fluorosulfonyl)imide.
4. The electrolyte according to claim 2 or 3, characterized in that The concentration of the lithium salt in the electrolyte is 0.5-2 mol / L.
5. The electrolyte according to claim 4, characterized in that The organic solvent includes cyclic carbonate and chain carbonate. The cyclic carbonate is any one or a combination of ethylene carbonate and propylene carbonate; the chain carbonate is any one or a combination of diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
6. The electrolyte according to claim 5, characterized in that The mass percentage of the cyclic carbonate added in the electrolyte is 25-35%.
7. The electrolyte according to claim 5, characterized in that The added mass percentage of the chain carbonate in the electrolyte is 52-58%.
8. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: It also includes the electrolyte as described in any one of claims 2 to 7.
9. A lithium ion battery according to claim 8, characterized in that: The positive electrode is a high-nickel positive electrode material.
Citation Information
Patent Citations
Electrolyte additive for electrolytic copper foil, high-resistance and high-ductility electrolytic copper foil and production method of high-resistance and high-ductility electrolytic copper foil
CN116590762A
Silicon-based energy storage devices with electrolyte containing cyanate based compounds
US20210249689A1